The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/ccr3.1350
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma pneumoniae‐associated Fuchs syndrome

Abstract: Key Clinical MessageFuchs syndrome is a milder form of the Stevens–Johnson syndrome (SJS) spectrum with only mucosal involvement which can be triggered by Mycoplasma pneumonia (MP) infection. Treatment should be directed toward supportive care including ocular and mucous membrane care, fluids and nutritional support, and pain control. In addition, antibiotic and immunomodulatory treatments are discussed for this entity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 3 publications
0
8
0
3
Order By: Relevance
“…El Mp es una causa común de neumonía extrahospitalaria, con manifestaciones mucocutáneas infrecuentes (25%) que tienden a afectar en su mayoría al sexo masculino, niños y adultos jóvenes [4][5][6][7][8][9] .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…El Mp es una causa común de neumonía extrahospitalaria, con manifestaciones mucocutáneas infrecuentes (25%) que tienden a afectar en su mayoría al sexo masculino, niños y adultos jóvenes [4][5][6][7][8][9] .…”
Section: Discussionunclassified
“…La afectación cutánea, a diferencia del EM mayor y SSJ, suele ser escasa, y de localización acral y está ausente en un tercio de los casos, lo que sugiere MIRM, ya que en la actual clasificación de EM-SSJ/NET no existe una categoría que contemple esta situación 2,6,11 . Las lesiones cutáneas más frecuentes son las vesículas o ampollas (77%) seguidas de las lesiones en diana (48%).…”
Section: Discussionunclassified
“…Previously, this clinical condition was classified within the epidermolytic dermopathy spectrum as "atypical SJS, " "incomplete SJS, " or "Fuchs syndrome" (5,10,11,14,15). Recently, a systematic review concluded that this condition was a distinct entity called Mycoplasma pneumoniae-induced rash and mucositis (MIRM) (11,(14)(15)(16)(17). However, no patient with MIRM has been reported in China until now, indicating that many clinicians had no knowledge of this disease and that such patients could be misdiagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…Mycoplasma -induced rash and mucositis is rare. Previously, this clinical condition was classified within the epidermolytic dermopathy spectrum as “atypical SJS,” “incomplete SJS,” or “Fuchs syndrome” ( 5 , 10 , 11 , 14 , 15 ). Recently, a systematic review concluded that this condition was a distinct entity called Mycoplasma pneumoniae -induced rash and mucositis (MIRM) ( 11 , 14 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…SJS is thought to fall within a spectrum of diseases that affect the skin and mucous membranes, including erythema multiforme minor, erythema multiforme major (or SJS), and toxic epidermal necrolysis [6, 10]. Mycoplasma pneumonia can be associated with isolated mucous membrane disease or in combination with skin involvement [11]. Many authors believe that M. pneumoniae -associated mucositis with the minimal or absence of skin lesions is a separate entity from SJS, labelled as atypical SJS or M. pneumoniae -induced rash and mucositis [3, 12].…”
Section: Discussionmentioning
confidence: 99%